The Effectiveness of Using Flipped Classroom Strategy ‎Program in the Development of Evaluation Competencies ‎and Habits of Mind for the Student-Teacher in Imam ‎Muhammad Ibn Saud Islamic University.‎ - Al-Shalabi, Ilham (Jordan Journal of Educational Sciences, 2017)
The research aimed to design and identify the effectiveness of using flipped classroom strategy program in the development of evaluation competencies (cognitive -performance) and habits of mind for the students in Imam Muhammad Ibn Saud Islamic University. Quasi-experimental method, based on the design (Pre- Post) for two groups (experimental, control) was used to answer questions of the research. The sample consisted of 54 students who were selected randomly; (28) as experimental group and (26) as control group from the 7th grade students in English major enrolled in the Measurement & Evaluation course. A program in light of flipped classroom strategy, achievement test, rating scales for evaluation competencies where developed, and habits of mind instrument were used. The results revealed that the program is effective in the development of evaluation competencies and habits of mind. The researcher recommended designing courses with activities and models in light of the flipped classroom strategy, and recommends training and encouraging staff members to use this strategy which increases the efficiency of the teaching process